Saving grace: distally pedicled gracilis muscular flap in lower limb salvage - Amin, Kavit (BMJ Publishing Group, 2014)
During the 1970s, the incidence of limb amputation following surgery for sarcoma excision was as high as 50%. Two important developments have led to modern day limb salvage, namely chemotherapy and precision imaging techniques. We present a case of limb salvage in a patient with osteosarcoma plagued with recurrent infection after prosthetic revision. We discuss the use of the distally based pedicled gracilis muscular flap, which has little mention as a reconstructive option for defects around the knee.